(untitled) (Czech Journal of International Relations, 2002)
Paul Rogers: Losing Control. Global Security in the Twenty-first Century. 1st ed. London: Pluto Press, 2000,164s.). Michael MccGwire: The paradigm that lost its way. International Affairs, Vol. 77, No. 4 /2001/, s. 777-803.